LENGTH AT FIRST MATURITY, SPAWNING TIME, AND REPRODUCTIVE OUTPUT IN THE FEMALES OF HAMILTONÃ¢â¬â¢S ANCHOVY (THRYSSA HAMILTONII GRAY, 1835) - Mohammad Mukhlis Kamal; Yunizar Ernawati; Nina Nurmalia Dewi (Jurnal Biologi Tropis, 2020)
Abstract: The HamiltonÃ¢â¬â¢s anchovy (Thryssa hamiltonii Gray, 1835) is one of main target species in Indonesian small pelagic fishery. This engraulids member is characterized by short lifespan and fast reproductive cycle. The research aims were to explore the reproduction aspects of the females HamiltonÃ¢â¬â¢s anchovy in terms of changes in length at first maturity, spawning seasons, and fecundity as well as egg diameter as reproductive output. Fish was collected weekly during 2009 at fish landing site at Gebang Mekar, Cirebon. The fish was length measured, after which ovaries staged for gonadal maturity stage (GMS), fecundity, and eggs diameter. Length frequency data was all linked to this reproductive aspects. The results showed that Lm was 171.5 ÃÂ± 1.62 mm, comparable to annual calculation of 171.05 ÃÂ± 0.01 mm, Lc largely tend to smaller than Lm which indicated to unsustainable fishing. Fish spawns monthly with fecundity range between 3,456 Ã¢â¬â 15,843 (8,261 ÃÂ± 2,776 eggs), it might be categorized as high fecundity fish relative to its body size. The distribution of eggs diameter showed 2-3 modus, i.e. they are partial spawner fish. The discrepancies in reproductive ouput is suggested to be influenced by seasons which characterized by different environmental conditions.ÃÂ Keywords: HamiltonÃ¢â¬â¢s anchovy, females, length, spawning, reproductive output